The Effect of the Shape of a Laboratory Scale Wind Power Generator in Generating Energy - Muhammad Yoga Amiansyah; Harry Ramza; Rosalina Rosalina (Sekolah Tinggi Teknik PLN, 2021)
In this study, the influence of the shape of the propellers of a laboratory-scale wind power plant on the energy produced will be measured. It is known that the number of propellers and wind speed greatly affect the energy produced. With this, researchers will conduct research on the influence of the shape of the propeller on the energy produced. with the aim of knowing the effect of the shape of the propeller on the energy produced. The methods used are literature studies and experiments where literature studies are carried out to find references to the problems raised, experimental research is to design tools and try out to find causal data. The results of this study indicate that flat-shaped propellers get or produce higher energy compared to thin and curved propellers. By experimenting on the fan in